2021
DOI: 10.1108/mbe-11-2020-0155
|View full text |Cite
|
Sign up to set email alerts
|

A bi-dimensional classification and characterization of enterprise social media users

Abstract: Purpose Enterprise social media (ESM) platforms are rapidly diffusing in the business context because they can bring substantial benefits to companies by enhancing their knowledge management (KM) processes. However, such benefits materialize only if active employee participation is ensured. Therefore, it is crucial to understand how individual employees use an ESM platform to assist their knowledge-related activities. This paper contributes to this topic by proposing a classification of ESM users based on two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Further demonstrating that lurking behavior is a continuum, both Gong et al (2015) and Malinen (2015) found that lurkers could be turned into postersand thus, treating lurkers as a fixed entity could be a mistake. Kirchner et al (2022) also found four unique user types within social media communities-frequent contributors, sporadic contributors, frequent lurkers, and sporadic lurkers (also often known as ghosts due to their lack of presence in the group). Walker et al (2010) suggested that the tendency to put zero and infrequent posters together into the lurker category contributes to some confusion about lurkers' benefits and behaviors.…”
Section: Lurkers Versus Postersmentioning
confidence: 93%
“…Further demonstrating that lurking behavior is a continuum, both Gong et al (2015) and Malinen (2015) found that lurkers could be turned into postersand thus, treating lurkers as a fixed entity could be a mistake. Kirchner et al (2022) also found four unique user types within social media communities-frequent contributors, sporadic contributors, frequent lurkers, and sporadic lurkers (also often known as ghosts due to their lack of presence in the group). Walker et al (2010) suggested that the tendency to put zero and infrequent posters together into the lurker category contributes to some confusion about lurkers' benefits and behaviors.…”
Section: Lurkers Versus Postersmentioning
confidence: 93%
“…The recent worldwide surge in social media platform users has substantially impacted the operations and procedures of organisations [10]. Organisations often embrace social media to accomplish various goals, such as information sharing, connection building, brand development, boosting awareness, and gathering customer insights [11]. In addition, the engagement of social media platforms within firms affects organisational decision-making processes and job skills.…”
Section: Introductionmentioning
confidence: 99%
“…Enterprise social media (ESM) is a broad term that refers to the use of social media networks by organisations in a variety of ways to achieve various business objectives, such as knowledge exchange and communication (Kirchner et al, 2021;Leonardi et al, 2013). ESM research has attracted significant attention from practitioners and researchers over the last decade owing to the range of advantages it provides to organisations in terms of communication and collaboration (Li et al, 2021;Sharma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Organisations are now using social media to achieve a range of objectives, including knowledge sharing, relationship building, brand building, raising awareness and gaining customer insights (Kirchner et al, 2021;Pitafi et al, 2018). Social media usage has increased significantly, especially in disaster and emergency situations to connect with others and share information on food, shelter and medical issues (Saroj and Pal, 2020;Sharma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation